Why use-centered game-based learning in higher education? the case of cesim simbrand - Costa, Gonçalo Jorge Morais da (2014)
This paper endeavours to research about simulation/serious games exploration within University of Algarve (Portugal), namely Cesim SimBrandfor Marketing Simulation (course unit). A total amount of 30 learners participated in this study through a mixed survey (openended and closed-ended queries). The empirical evidences exhibit interesting outcomes: (i) a response rate of 50 percent; (ii) these tools increase learning engagement, although it is essential to be more realistic; (iii) teamwork seems to be a controversial topic; (iv) learners had a positive experience; however, some feel unprepared before their usage (prior knowledge). Hence, this survey provides a good platform for future research and approaches how to promote a better exploration of simulation/serious games. To conclude, this manuscript will be divided into six sections: (i) the 5W’s of game-based learning; (ii) research (statement of the problem, aims/objectives, philosophical approach and data collection/analysis); (iii) diagnosis (game deliver and learners’ pre-perception); (iv) findings (learners’ profile, awareness, experiences and preparation); (v) limitations and future work (methodological limitations and tools/analysis upgrade); and, (vi) conclusions.